In Vivo Evaluation of a Gastro-Resistant HPMC-Based "Next Generation Enteric" Capsule - Adrian Rump; Marie-Luise Kromrey; Eberhard Scheuch; Vincent Jannin; Lara Rehenbrock; Mladen Vassilev Tzvetkov; Werner Weitschies; Michael Grimm (MDPI AG, 2022)
Many orally dosed APIs are bioavailable only when formulated as an enteric dosage form to protect them from the harsh environment of the stomach. However, an enteric formulation is often accompanied with a higher development effort in the first place and the potential degradation of fragile APIs during the coating process. Ready-to-use enteric hard capsules would be an easily available alternative to test and develop APIs in enteric formulations, while decreasing the time and cost of process development. In this regard, Lonza Capsugel® Next Generation Enteric capsules offer a promising approach as functional capsules. The in vivo performance of these capsules was observed with two independent techniques (MRI and caffeine in saliva) in eight human volunteers. No disintegration or content release in the stomach was observed, even after highly variable individual gastric residence times (range 7.5 to 82.5 min), indicating the reliable enteric properties of these capsules. Seven capsules disintegrated in the distal part of the small intestine; one capsule showed an uncommonly fast intestinal transit (15 min) and disintegrated in the colon. The results for this latter capsule by MRI and caffeine appearance differed dramatically, whereas for all other capsules disintegrating in the small intestine, the results were very comparable, which highlights the necessity for reliable and complementary measurement methods. No correlation could be found between the gastric residence time and disintegration after gastric emptying, which confirms the robust enteric formulation of those capsules.